Discursos dos usuários dependentes de substâncias psicoativas sobre sua imagem discursivamente construída - Acorinte, Ana Carolina (2017)
The constitution of the discourse of the drug user about his image, his place and position is determined by social and historical conditions, as well it can be filled by others previous discourses, crossed by the dominant senses of the biological, manicomial and moral pattern, which can appoint the image he has about himself and about his position as a position-subject. The purpose of this study was analyzing the discourse of the alcohol users and other drugs users in treatment in CAPD AD, it was about the image he has of himself as a subject addicted to psychoactive substances, the image of the other addicted people and the place and position conceived by him. In order to get this purpose, we are based on a methodological and theorical reference which would include the ideological processes and the imaginative formations that the alcohol and other drugs users have about themselves and about their disease. Thus, this theoretical reference was based on French Discourse Analysis, constructed upon the theory of Michel Pêcheux. It is a qualitative research, developed in CAPS AD in the city of São Carlos, São Paulo. Twelve psychoative substances users who are treated by the mental heathy service participated in this study. We used a half structured interview script for data collecting and a recorder to have the conversation saved. As a result, it emerged two discursive blocks: the images which the psychoactive substances user in treatment has about himself and the discourse of the society about this subject who is psychoactive substances addicted to. It was concluded that the ideological effect and the naturalization of some senses is the interpretation that the drug user is rejected and harassed because he is a deviant person and that the speech of this subject from an evocated ideology of his discursive memory is filled by de biomedical and moral pattern.